LANGUAGE DIDACTIC PRINCIPLES OF CULTURE FORMATION OF PEDAGOGICAL COMMUNICATION OF FUTURE TEACHERS PRIMARY CLASSES (Pedagogy of Higher and Secondary Education, 2010)
In article features of formation of culture of pedagogical dialogue of the future teachers of elementary grades are considered; is professional - communicative abilities of the future teachers are defined and described.